Chic samrtie HTC Touch Pro. - Oliveros, Luis Anthony G. (PC World Philippines)
Overall, the HTC Touch Pro may be an investment, but you get what you're paying for; an impressive build quality and high-end design that matches its expensive list of features and an interface that improves the user experience.